Leaf Morphological and Nutrient Traits of Common Woody Plants Change Along the Urban–Rural Gradient in Beijing, China - Su, Yuebo; Renz, Mark; Cui, Bowen; Sun, Xu; Ouyang, Zhiyun; Wang, Xiaoke (Frontiers in Plant Science, 2021)
An increasing number of studies have found differences in plant functional traits between urban and rural sites as a result of urbanization. However, the results remain inconsistent. In this study, we measured morphological and nutrient traits of 11 common woody plants along a continuous urban–rural gradient in Beijing, China. Leaf size (e.g., length, width, and area), specific leaf area, and leaf nitrogen and potassium contents decreased gradually and significantly along the urban–rural gradient, indicating that urbanization can enhance plants’ capacity to acquire resources for growth and production. Further, soil nutrients and air temperature decreased along the urban–rural gradient, while air relative humidity increased. A structural equation model showed that these alterations in physical factors attributable to urbanization contributed directly or indirectly to changes in leaf functional traits, implying that changes in soil nutrients and micro-climate induced by urbanization may affect plant growth and production because of the improvement in resource acquisition capacity.